2005
DOI: 10.1017/s002211200500337x
|View full text |Cite
|
Sign up to set email alerts
|

The stratified Boycott effect

Abstract: We present the results of an experimental investigation of the flows generated by monodisperse particles settling at low Reynolds number in a stably stratified ambient with an inclined sidewall. In this configuration, upwelling beneath the inclined wall associated with the Boycott effect is opposed by the ambient density stratification. The evolution of the system is determined by the relative magnitudes of the container depth, h, and the neutral buoyancy height, h n = c 0 (ρ p − ρ f )/|dρ/dz|, where c 0 is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…At low Reynolds numbers, instabilities that lead to fluctuations have been observed [91,92], in particular in sedimentation of polydisperse suspensions [93] and in a stratified ambient [94]. An analysis of those phenomena in the framework of kinematic-wave theory seems to be lacking, but is beyond the scope of the present paper.…”
Section: Initial Conditions and Instabilitiesmentioning
confidence: 87%
“…At low Reynolds numbers, instabilities that lead to fluctuations have been observed [91,92], in particular in sedimentation of polydisperse suspensions [93] and in a stratified ambient [94]. An analysis of those phenomena in the framework of kinematic-wave theory seems to be lacking, but is beyond the scope of the present paper.…”
Section: Initial Conditions and Instabilitiesmentioning
confidence: 87%
“…This could induce convection currents (Boycott effect, e.g. Peacock et al, 2005) but this should not alter the observed frother-type effect. Recent work holding bubbles stationary in down-flowing water continues to support this frother-type effect on fine bubbles (Navarra et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the mechanisms of oil-water-solid gravity separation include the principles of Stokes' Law (Perry and Green, 1997) and the boycott effect (Peacock et al, 2005). Oil and solids in water are characterized by a spectrum of droplet sizes.…”
Section: Iviateriais and Metbodsmentioning
confidence: 99%